The Effect of Storage Condition and Duration on the Deterioration of Primed Rice Seeds - Wang, Weiqin; He, Aibin; Peng, Shaobing; Huang, Jianliang; Cui, Kehui; Nie, Lixiao (Frontiers in Plant Science, 2018)
Abstract Seed priming is a successful practice to improve crop establishment under adverse environment. However, reduced longevity of primed rice (Oryza sativa L.) seeds during storage limited the adoption of this technique. Present study investigated the effect of temperature, relative air humidity (RH) and oxygen on the longevity of primed rice seeds in a range of 60 days storage. In addition, the biochemical and morphological mechanisms associated with deterioration of primed seeds during storage were explored. Three types of priming treated rice seeds and one non-primed control were stored under 1) low temperature-vacuum (LT-V), 2) room temperature-vacuum (RT-V), 3) room temperature-aerobic-low RH (RT-A-LH) and 4) room temperature-aerobic- high RH (RT-A-HH) for 0, 15, 30, 45 and 60 days. The results showed that storage of seeds under different conditions for 15-60 days did not influence the longevity of non-primed rice seeds. Meanwhile, the viability of primed rice seeds did not reduce when stored under LT-V, RT-V and RT-A-LH, but was significantly reduced under RT-A-HH. Under vacuum condition, the increases of storage temperature (30℃) did not reduce the longevity of primed seeds. Likewise, the oxygen did not influence the longevity of primed rice seeds stored under low RH. Nevertheless, increase of RH significantly reduced the viability of primed seeds stored for 15-60 days. Reduced starch metabolism, the consumption of starch reserves in rice endosperms, the accumulation of malondialdehyde and the decreases of antioxidant enzyme activities might be associated with the deterioration of primed rice seeds during storage. In conclusion, storage of primed seeds under high RH condition beyond 15 days is deteriorative for germination and growth of rice. The primed rice seeds are recommended to store at vacuum or low RH or low temperature condition to ensure good crop establishment.